MENGOPTIMALKAN VARIASI SIZE SHOT KAMERA PADA FEATURE “THE OTHER SIDE OF NGLANGGERAN” - Erik Pratama; Halla Sayyidah Muflichah; Fadeyanto Prabowo (Jurnal Ilmu Komunikasi AKRAB, 2023)
ABSTRACTThe Other Side of Nglanggeran is a sidebar feature work. This program discusses the other side of the Ancient Volcano as a milestone in the establishment of the Nglanggeran Tourism Village using a geological perspective, the perspective of Pokdarwis, and community leaders. discusses how residents uphold their culture and are able to collaborate with the natural heritage that is given, with a duration of 24 minutes which is divided into 3 segments. The aim of this program is to provide information to get to know and dig a little deeper into the background of the success of a tourism village. The cameraman has responsibility for all visual aspects in the form of recording images. The author as a cameraman chooses to optimize the size shot variations. This technique has shooting distances such as extreme long shots, long shots, medium shots, medium close ups, close ups, and extreme close ups. The aim of optimizing the variation in shot size is so that the audience gets the beauty, message, and moments that the production team presents because every size shot has its own message and impression.Keywords: Nglanggeran, Feature, Cameraman, Shot variations